Intersectoral strategies between health and education for preventing adolescent pregnancy in Chile: Findings from a qualitative study. (5th October 2018) - Obach, Alexandra; Sadler, Michelle; Cabieses, Báltica
Abstract: Background: In Chile, despite its steady decrease overall, adolescent pregnancy is concentrated in the most vulnerable population. Efforts in intersectoral collaboration between health and education to address the problem are being developed, but they have not been assessed. Objective: To describe intersectoral strategies between health and education to address adolescent sexual and reproductive health, prevent adolescent pregnancy, and to explore adolescents' and health professionals' perceptions regarding those strategies. Design: A qualitative ethnographic study was carried out in five municipalities in the Metropolitan Region of Chile. A sample of five key informants, 23 health professionals and 50 adolescents participated in a total of 38 semi‐structured interviews and five discussion groups. Results: Two intersectoral strategies to respond to adolescents' sexual and reproductive health needs were identified: (a) the "in‐and‐out" strategy, where health professionals provide health care mostly in health centres and carry out specific actions in schools and (b) the school‐based strategy in which health professionals carry out continuous actions in schools as part of the curriculum. The second is perceived as responding better to adolescents' needs in sexual and reproductive health issues and in preventing adolescent pregnancy. Discussion: The school‐based strategy, with the constant presence of health professionals and lack of bureaucratic procedures, facilitates adolescents to access sexual and reproductive health care. This strategy enables sexual and reproductive health to be understood as an integral dimension of adolescents' lives, and it reinforces a holistic idea of health in which it is approached as a whole.